Notes on the Genus Parastasia Westwood, 1841 from Thailand (Coleoptera: Scarabaeidae, Rutelinae) - Hongsuwong, Thitipong; Phothaworn, Chayaphol (Fragmenta entomologica, 2025)
This paper presents new records from Thailand for four species of Scarabaeidae Rutelinae: Parastasia asahi Wada, 2008, P. burmeisteri Ohaus, 1898, P. dimidiata Erichson, 1845, and P. kraatzi Ohaus, 1900. A list of all Parastasia species occurring in Thailand is provided. Additionally, behavioral notes on some species of genus Parastasia are included and discussed.